EH domain proteins Pan1p and End3p are components of a complex that plays a dual role in organization of the cortical actin cytoskeleton and endocytosis in Saccharomyces cerevisiae. - Tang, H Y (1997)
Several proteins from diverse organisms have been shown to share a region of sequence homology with the mammalian epidermal growth factor receptor tyrosine kinase substrate Eps15. Included in this new protein family, termed EH domain proteins, are two yeast proteins, Pan1p and End3p. We have shown previously that Pan1p is required for normal organization of the actin cytoskeleton and that it associates with the actin patches on the cell cortex. End3p has been shown by others to be an important factor in the process of endocytosis. End3p is also known to be required for the organization of the actin cytoskeleton. Here we report that Pan1p and End3p act as a complex in vivo. Using the pan1-4 mutant which we isolated and characterized previously, the END3 gene was identified as a suppressor of pan1-4 when overexpressed. Suppression of the pan1-4 mutation by multicopy END3 required the presence of the mutant Pan1p protein. Coimmunoprecipitation and two-hybrid protein interaction experiments indicated that Pan1p and End3p associate with each other. The localization of Pan1p to the cortical actin cytoskeleton became weakened in the end3 mutant at the permissive temperature and undetectable at the restrictive temperature, suggesting that End3p may be important for proper localization of Pan1p to the cortical actin cytoskeleton. The finding that the pan1-4 mutant was defective in endocytosis as severely as the end3 mutant under nonpermissive conditions supports the notion that the association between Pan1p and End3p is of physiological relevance. Together with results of earlier reports, these results provide strong evidence suggesting that Pan1p and End3p are the components of a complex that has essential functions in both the organization of cell membrane-associated actin cytoskeleton and the process of endocytosis.